2010
DOI: 10.1039/c0dt00315h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of molybdenum imido alkylidene bis-pyrazolide complexes

Abstract: Reaction of Li(3,5-R(2)-pyrazolide) (R = tBu or Ph, dXpz) with Mo(NAr)(CHCMe(2)Ph)(OTf)(2)(DME) yields Mo(NAr)(CHCMe(2)Ph)(dXpz)(2) in good yield. These complexes react with alcohols or the surface silanols of silica, to yield bis-alkoxy and surface mono-siloxy alkene metathesis catalysts, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…An alternative strategy has focused on the direct grafting of molecular alkylidene complexes onto the surface of oxide supports. Preliminary reports appeared in early 2000s, and the application of modern characterization techniques eventually allowed for precise control of the structures of these surface species and gave rise to the generation of remarkably active well‐defined silica‐supported Mo‐ and W‐imido‐alkylidenes and more recently W‐oxo‐alkylidenes (Section 7.3.2.4). In the 1970s and 1980s the groups of Yermakov and Iwasawa were the first to use organometallic precursors (Mo(C 3 H 5 ) 4 and W(C 4 H 7 ) 4 ) to prepare well‐defined supported Mo and W oxides relevant to industrial systems and discriminate the activities of different oxidation states.…”
Section: Alkene Metathesismentioning
confidence: 94%
See 2 more Smart Citations
“…An alternative strategy has focused on the direct grafting of molecular alkylidene complexes onto the surface of oxide supports. Preliminary reports appeared in early 2000s, and the application of modern characterization techniques eventually allowed for precise control of the structures of these surface species and gave rise to the generation of remarkably active well‐defined silica‐supported Mo‐ and W‐imido‐alkylidenes and more recently W‐oxo‐alkylidenes (Section 7.3.2.4). In the 1970s and 1980s the groups of Yermakov and Iwasawa were the first to use organometallic precursors (Mo(C 3 H 5 ) 4 and W(C 4 H 7 ) 4 ) to prepare well‐defined supported Mo and W oxides relevant to industrial systems and discriminate the activities of different oxidation states.…”
Section: Alkene Metathesismentioning
confidence: 94%
“…[519][520][521][522][523][524][525][526] Supporteda lkylidynes were also shownt o be active metathesis catalystp recursors. Preliminaryr eports appeared in early2 000s, [541,542] andt he applicationo fm odern characterization techniques eventually allowedf or precise controlofthe structures of thesesurface speciesand gave rise to theg enerationo fr emarkablya ctive well-defined silica-supportedMo- [543][544][545][546][547][548][549] andW-imido-alkylidenes [550][551][552][553][554][555] andmore recently W-oxo-alkylidenes [556][557][558][559][560] (Section 7.3.2.4).I nt he 1970sa nd 1980st he groups of Yermakov [561][562][563][564] andI wasawa [565,566] were thef irst to useo rganometallicp recursors (Mo(C 3 H 5 ) 4 and W(C 4 H 7 ) 4 )t op repare well-defined supported Mo and Woxides relevant to industrial systems and discriminate the activities of different oxidation states.T hese studies suggested that neither fully oxidized Mo VI /W VI nor highly reduced Mo II /W II species were responsible for the metathesis activity and that active sites likely arose from the oxidation state + IV.Recent advances in describing the redox chemistry of well-defined supported W-oxo sites in relation to alkene metathesis are discussed in Section 7.3.2.5. [441] Supportedt ungstenh ydridesr epresent as pecial classo fi nsitug enerated olefin m...…”
Section: Surface Sites In Industrial Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine alternative Strategie konzentrierte sich auf das direkte Verankern molekularer Alkylidenkomplexe auf der Oberfläche von Oxidträgern. Berichte hierzu erschienen bereits in den frühen 2000er Jahren, aber erst durch die Anwendung moderner Charakterisierungsverfahren konnten die Strukturen dieser Oberflächenspezies genau bestimmt und außerordentlich aktive, gut definierte Mo‐ und W‐Imido‐Alkylidene und aktueller W‐Oxo‐Alkylidene auf Siliciumdioxidträgern hergestellt werden (Abschnitt 7.3.2.4). In den 1970er und 1980er Jahren verwendeten Yermakov und Iwasawa erstmals metallorganische Vorstufen (Mo(C 3 H 5 ) 4 und W(C 4 H 7 ) 4 ) zum Herstellen gut definierter Mo‐Oxid‐ und W‐Oxid‐Trägerkatalysatoren, die für industrielle Systeme interessant sind, und zum Unterscheiden der Aktivitäten verschiedener Oxidationsstufen.…”
Section: Alkenmetatheseunclassified
“…Ersetzen des Alkyl‐X‐Liganden in (≡SiO)Mo(=NAr)(=CH t Bu)(X) durch ein Alkoxid oder Amid erhöht die Selektivität und Stabilität der Katalysatoren. Schema a zeigt die aktuelle Familie der gut definierten, Mo‐Imido‐Alkylidene auf Siliciumdioxidträgern, einschließlich Komplexe mit verschiedenen Amid‐ (X=Ph 2 N, Pyrrolyl, 2,5‐Dimethylpyrrolyl (Me 2 Pyr), Pyrrazolyl) und Alkoxid‐X‐Liganden (X=O t Bu, OC(CF 3 ) 2 Me, OC(CF 3 ) 3 , O‐2,6‐ i Pr 2 C 6 H 3 ) . Variation des Imidoliganden bietet einen zusätzlichen Weg zum Einstellen der Aktivität des Katalysators .…”
Section: Alkenmetatheseunclassified